Sport consumption patterns in the Eastern Cape: cricket spectators as sporting univores or omnivores - Brock, Kelcey (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2015)
Since its inception, consumption behaviour theory has developed to account for the important social aspect that underpins or at least to some extent can be used to explain consumption behaviour. Modern consumption behaviour theory is anthropocentric in nature, with people and societal influence at the forefront of the theory. To date, empirical studies on consumption behaviour of cultural activities (for example, music and arts), entertainment and sport have used Bourdieu's (1984) omnivore/univore theory to suggest that consumption of leisure activities is bound up in social ties. To date, no such investigation has been conducted in the context of sport in South Africa. The aim of the study therefore is to investigate whether South African cricket spectators are sporting omnivores or univores, thus, essentially investigating whether sports consumption behaviour in South Africa is bound up in social ties. A number of positive economic and social ramifications could result from gaining a holistic understanding of sports consumption behaviour in South Africa. Given these ramifications, the secondary goal of the research is to identify motives for consumers making specific sport consumption decisions, and determining whether certain characteristics can be attributed to these consumption decisions. Recommendations based on the findings of the research could help various stakeholders understand sports consumption patterns in South Africa, which could in turn lead to the realization of positive economic and social benefits. The study made use of a questionnaire, administered at four different limited overs cricket matches in the 2012/13 cricket season, to obtain a range of responses reflecting specific types of consumption behaviour as well as motives for consumption decisions of cricket spectators in the Eastern Cape. Using individual binary probit models and post estimation F-tests, the results indicate that consumption behaviour of sport within South Africa predominantly differs on the grounds of education and race. This suggests that there are aspects of social connotations underpinning sports consumption behaviour within South Africa
Keywords: Cricket -- South Africa -- Eastern Cape; Cricket -- Social aspects; Consumption (Economics); Consumer behavior